Inventive Step vis-à-vis Non-Obviousness - Rethinking Section 2(1)(ja) of the Indian Patents Act, 1970 (Journal of Intellectual Property Rights (JIPR), 2024)
Inventive step is the sine qua non for the grant of a patent. Arguably, this subjective evaluation of the claimed inventionensures a sufficient leap forward to the existing technology. The footnote appended to Article 27 of the TRIPS Agreementcontemplates that inventive step may be deemed tobe synonymous with“non-obvious”. Thus, the footnote has left it openendedfor the WTO members to speculate on may or may not situations or entirely rule out this apparent inventive step/nonobviousnessequivalence suggestion. TRIPS Agreement does not define inventive step or lay down the standards to befollowed in construing the person from whose perspective the claimed invention has to be looked into for inventivestep/non-obviousness determination. In the U.S., Congress and the Courts have consistently interpreted “non-obviousness”as technical advancement to the concerned discipline. When it comes to Indian law, there is an apparentclarity, but whendelved deep, the outcome lacks crucial elements of predictability. Section 2(1)(ja) of the Indian Patents Act, 1970 is framedin such a way so that it gives an impression to the reader that technical advancement and being non-obvious to a personskilled in the art are two distinct concepts. The US Courts always gave economic considerations a secondary status in thedetermination of the non-obviousness of a given invention. Indian patent statute specifically mentions economicsignificanceand places it as an alternative to technical advancementwithoutclarifying the interconnection of the twoconnotations.The authors intend to understand, in what way technical advance can be considered as a completely separatestandalone criterion for patentability in conjunction with non-obviousness. Furthermore, as a step forward, the authors wantto expound on whether economic consideration alone,without even requiring non-obviousness, can fulfil the inventive stepcriterion in India.